Robust design of thermo-mechanical MEMS switch embedded in aluminium BEOL interconnect. Issue 9 (August 2015) - Orellana, S.; Arrazat, B.; Fornara, P.; Rivero, C.; Blayac, S.; Montmitonnet, P.; Inal, K.
Abstract: A new concept of a thermo-mechanical lateral switch activation is proposed. Embedded in standard aluminium BEOL (Back End Of Line), it is fully integrated in CMOS technology. The simplicity of this low cost one-mask fabrication allows the straightforward scalability of design. Most functional problems have been solved through process, simulation and design: stiction, bending, displacement, and robustness. The present study of a thermo-mechanical MEMS switch focuses on three points. Firstly, the design is modified to increase the apparent area contact and the force applied. Secondly, in order to ensure the reversibility of the movement, a running-in step before operation is implemented. Finally, a new design is proposed, simulated and manufactured to avoid the undesirable activations by spurious homogeneous heating. Highlights: A new concept of a thermo-mechanical lateral switch activation is proposed - fully integrated in CMOS technology. The study of thermo-mechanical MEMS switch focuses on three points: Design modification to increase the apparent area contact and the force applied. Running-in step before operation was validate. Design to avoid the undesirable activations by spurious homogeneous heating.